Application of 1 nm gold probes on paraffin wax sections for in situ hybridisation histochemistry. Issue 10 (October 1990) - Jackson, P; Dockey, D A; Lewis, F A; Wells, M
Abstract : An in situ hybridisation technique that uses 1 nm immunogold reagents and silver enhancement was devised to detect biotinylated DNA viral probes in formalin fixed, paraffin wax sections of human cervix. DNA probes labelled with biotin-11-deoxyuridine triphosphate were detected after hybridisation to nucleic acid sequences by an antibiotin antibody, followed by a gold labelled secondary antibody. Silver enhancement then permitted visualisation of the signal at the light microscopic level. The method was reliable and produced less background staining than previously described methods. The signal could be enhanced by epi polarisation microscopy. Furthermore, biotinylated DNA probes may be detected directly by a 1 nm gold labelled goat antibiotin antibody without loss of labelling intensity, and this may be preferable to the longer two layer technique, previously described.